HUMANISTIC HARMONY OF EDUCATIONAL PROCESS - A RELIABLE BASIS OF DEVELOPMENT STUDENT PERSONALITIES - Yu.V. Reva (Academy of Cognitive and Natural Sciences, 2022)
This work deals of the essence of harmony of the educational process as the reliable basis of the development of the person. The ways, conditions and technologies of its realization are shown.